Peningkatan Kemampuan Berpikir Siswa Pondok Pesantren Alam Sayang Ibu Melalui Penerapan Metode BHATATSA - Aydatul Munawwarah; Syamsul Arifin (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2024)
ABSTRACT The purpose of this study was to explain the application of the BHATATSA method in improving students' critical thinking skills at the Alam Sayang Ibu Islamic boarding school. The BHATATSA method is implemented through Qur'an diary activities. This research applies a qualitative descriptive approach to describe in detail the data to be sought. The data in this study were obtained through observation, supported by in-depth interviews and documentation from several sources, namely the head of the Alam Sayang Ibu Islamic boarding school, the coordinator of the Qur'an diary activity, the Qur'an diary teachers and also the students involved in the Qur'an diary activity. The results showed that the implementation of the BHATATSA method can train and improve the critical thinking of students of the Alam Sayang Ibu Islamic Boarding School through various analyzing activities summarized in the BHATATSA method. Keywords: Method, BHATATSA, Critical Thinking